Sosialisasi dan Pendampingan dalam Pembuatan NIB melalui OSS di Desa Sumberbendo Kabupaten Probolinggo - Ervin Ghozi Halim; Dita Puspita Septyaningrum; Silvia Nadhifa Mawarni Dirgantari; Indira Arundinasari (Cv. Utility Project Solution, 2023)
Micro, Small and Medium Enterprises (MSMEs) are trading or commerce activities that are widely circulated in Indonesia. Many of these commercial activities are carried out by the community, especially individuals or business entities. With the large number of people who set up MSMEs, it also creates new problems. The problem is that many of the MSME players do not have a Business Identification Number (NIB). With this problem, KKNT students conducted socialization and also assistance for MSME players to get NIB. This activity was carried out in Sumberbendo Village, Sumberasih District, Probolinggo Regency. The methods used in this community service activity are observation, implementation, and submission of NIB. This activity is carried out door to door by visiting the residence of MSME owners so that business actors can understand more about NIB. The process of making NIB is carried out through the Online Single Submission website, which is an integrated electronic system from the government. The results of this activity, which took place smoothly and MSME players in Sumberbendo Village managed to get NIB without any obstacles.